Inside Back Cover: Salt Metathesis: Tetrafluoroborate Anion Rapidly Fluoridates Organoboronic Acids to give Organotrifluoroborates (Angew. Chem. Int. Ed. 16/2023). Issue 16 (15th March 2023) - Lozada, Jerome; Xuan Lin, Wen; Cao‐Shen, Rosana M.; Astoria Tai, Ruyin; Perrin, David M.
Abstract : Salt metathesis and BFX (boron–fluoride exchange) of BF4 − with boronic acids generates RBF3 − derivatives, thus showing the solvolytic lability of BF4 − that enables its use as a fluorinating agent, even though many highly reactive reagents employ BF4 − as a non‐reactive counteranion. In their Research Article (e202215371), David M. Perrin and co‐workers report the synthesis of RBF3 − derivatives via a salt metathesis reaction using a series of MBF4 salts in methanol. This work highlights the proclivity of BF4 −, generally considered weakly coordinating and unreactive, to rapidly fluorinate boronic acids.